Kajian Dampak Alih Fungsi Lahan Sawah terhadap Struktur Mata Pencaharian Masyarakat di Kecamatan Cianjur Kabupaten Cianjur - Muhamad Arpi Darajat; Yulia Asyiawati (Bandung Conference Series: Urban & Regional Planning, 2022)
Abstract. Land conversion is a change in the function of land which was originally agricultural land turned into settlements or other physical buildings. Land conversion is considered to be a big problem when it results in environmental damage and affects the economic structure of the community. Rice fields in Cianjur District are designated as LP2B. Then with adequate road infrastructure, it is used as an indication of one of the factors causing changes in the economic livelihoods of the people in Cianjur District.This study aims to identify the impact of the conversion of paddy fields on the structure of community livelihoods in Cianjur District, while the method used in this research is a quantitative method. Data collection techniques through observation, interviews and questionnaires. The analytical method in this study uses the overlay analysis method and simple regression analysis.The conclusion of this study is the shift in land use change in Cianjur District in a period of 5 - 10 years where the conversion rate is 10% to 14%, then the tendency of land change is more towards paddy fields that have been facilitated by good road infrastructure, and the impact of land conversion The function of paddy fields affects the livelihoods and income of the community in Cianjur District. Abstrak. Alih fungsi lahan merupakan perubahan fungsi lahan yang awalnya merupakan lahan pertanian berubah menjadi permukiman atau bangunan fisik lainnya. Alih fungsi lahan dianggap menjadi persoalan besar ketika berakibat pada kerusakan lingkungan dan menyentuh terhadap struktur perekonomian masyarakat. Lahan sawah di Kecamatan Cianjur ditetapkan sebagai LP2B. Kemudian dengan prasarana jalan yang memadai dijadikan indikasi salah satu faktor penyebab perubahan mata pencaharian ekonomi masyarakat di Kecamatan Cianjur.Dalam penelitian ini bertujuan untuk mengidentifikasi dampak alih fungsi lahan sawah terhadap Struktur Mata Pencaharian Masyarakat di Kecamatan Cianjur, adapun metode yang digunakan dalam peneliltian ini adalah metode kuantitatif. Teknik pengumpulan data melalu observasi, wawancara dan kuesioner. Metode analisis dalam penelitian ini menggunakan metode analisis overlay dan analisis regresi sederhana. Hasil kesimpulan dari penelitian ini adalah pergeseran perubahan penggunaan lahan di Kecamatan Cianjur dalam periode 5 – 10 tahun yang mana laju konversi sebesar 10% sampai 14%, lalu kecenderungan perubahan lahannya lebih mengarah kepada lahan sawah yang sudah terfasilitasi prasarana jalan yang baik,dan dampak alih fungsi lahan sawah berpengaruh terhadap mata pencaharian dan pendapatan masyarakat di Kecamatan Cianjur.